Anaesthetic management of thoraco‐omphalopagus twins with congenital heart disease for separation surgery. Issue 1 (6th April 2017) - Dogar, Samie; Hamid, Muhammad; Khan, Ausaf; Shamim, Faisal; Khan, Fauzia
Summary: Conjoined twins' separation surgery poses challenges to anaesthetists due to the variable degree of cross circulation, difficulty in positioning, bleeding and limitations of space for sharing between two anaesthetic teams. We present the anaesthetic management for separation surgery of three‐months old conjoined twins. Both babies had congenital heart disease, with one baby hypertensive and commenced on enalpril pre‐operatively. A pre‐operative multi‐disciplinary meeting between all stake holders and a full environment simulation was performed and was helpful. The problems encountered included difficulty in percutaneous central venous line placement requiring surgical cut down and intra‐operative bleeding requiring vasopressor therapy and postoperative intensive care unit stay.